Choroba psychiczna - cierpienie, które zmieniło prawo - Kmieciak, Błażej (ETHICS IN PROGRESS, 2014)
Throughout history, patients of psychiatric institutions were often treated improperly. These individuals were isolated, humiliated and excluded. On the other hand treatment frequently contravenes the subjective/agentrelative positions and rights of people with mental disorders in implementing so-called positive changes. The perception of improper handling of cited group of patients sometimes constituted the beginning stage of the activities, aimed at taking responsible care of people with schizophrenia or depression. That concern also has a unique character, involving the necessity to continue to take coercive action against the patient. The paper is intended to depict the past and current situation of psychiatric institution patients. It will also present the fundamental principles that currently exist for the protection of the rights of people treated in these hospitals.